Sympathetic transduction in humans: recent advances and methodological considerations - Young, Benjamin E.; Greaney, Jody L.; Keller, David M.; Fadel, Paul J. (American journal of physiology. Heart and circulatory physiology, 2021)
Ever since their origin more than one half-century ago, microneurographic recordings of sympathetic nerve activity have significantly advanced our understanding of the generation and regulation of central sympathetic outflow in human health and disease. For example, it is now appreciated that a myriad of disease states exhibit chronic sympathetic overactivity, a significant predictor of cardiovascular morbidity and mortality. Although microneurographic recordings allow for the direct quantification of sympathetic outflow, they alone do not provide information with respect to the ensuing sympathetically mediated vasoconstriction and blood pressure (BP) response. Therefore, the study of vascular and/or BP responses to sympathetic outflow (i.e., sympathetic transduction) has now emerged as an area of growing interest within the field of neural cardiovascular control in human health and disease. To date, studies have primarily examined sympathetic transduction under two distinct paradigms: when reflexively evoking sympatho-excitation through the induction of a laboratory stressor (i.e., sympathetic transduction during stress) and/or following spontaneous bursts of sympathetic outflow occurring under resting conditions (i.e., sympathetic transduction at rest). The purpose of this brief review is to highlight how our physiological understanding of sympathetic transduction has been advanced by these studies and to evaluate the primary analytical techniques developed to study sympathetic transduction in humans. We also discuss the framework by which the assessment of sympathetic transduction during stress reflects a fundamentally different process relative to sympathetic transduction at rest and why findings from investigations using these different techniques should be interpreted as such and not necessarily be considered one and the same.